Nutrient removal and biofuel potential of MaB-floc biomass from an integrated algal pond system treating domestic sewage - Sibelo, Linda (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2020)
Integrated algal pond systems (IAPS) are a passive water treatment technology derived from the Oswald designed advanced integrated wastewater pond systems (AIWPS®) and effect wastewater treatment based on biological activity of microorganisms within the system, solar energy and gravity. The technology consists of an advanced facultative pond (AFP), a series of interconnected high rate algal oxidation ponds (HRAOP) and algal settling ponds. The symbiotic relationship between microalgae and bacteria facilitated by paddlewheel mixing of HRAOP results in the formation of biomass aggregates known as MaB-flocs. MaB-floc formation enhances nutrient abstraction, gravitational sedimentation and separation from water hence forming two product streams; recyclable water and biomass, both with valorisation potential. This work aimed to determine the suitability of MaB-floc biomass generated in the HRAOP of an IAPS treating domestic sewage as feedstock for biofuel production based on the content of carbohydrate and lipid. Nutrient removal efficiency, biomass productivity and bulk lipid and carbohydrate concentration were monitored for two consecutive three-month periods in the winter and summer seasons of 2018/19. Maximum removal efficiencies of nitrogen and phosphorus were determined as 71% and 75% respectively, demonstrating the efficiency of IAPS as a wastewater treatment technology. MaB-floc biomass productivity in winter and summer was 9.4 g/m2/d and 16.5 g/m2/d respectively indicating the heavy influence of seasonal temperature, possibly day length, and solar irradiation on biomass productivity in the HRAOP. Summer productivity was lower than the maximum theoretical productivity of 25 g/m2/d possibly due to photoinhibition of photosynthesis as well as grazing pressures caused by the proliferation of rotifers mainly of the Brachionus genus. MaB-floc biomass consistently contained higher amounts of carbohydrate than lipid despite the changes in species dominance from Scenedesmus sp. and Desmodesmus sp. in winter to Pediastrum sp. in summer. Variations in MaB-floc biomass carbohydrate content were linked to changes in nitrogen concentration, mainly in the form of nitrates. Lower nitrogen concentration significantly increased the carbohydrate content of MaB-floc biomass from 17.5 ± 0.15% to 33.5 ± 0.3 % recorded in summer. In winter, biomass carbohydrate increased from 18.3 ± 1.2% to 35.8 ± 0.3%.To induce accumulation of carbohydrates through nitrogen starvation, isolated microalgal species native to the HRAOPs of the IAPS at Institute for Environmental Biotechnology Rhodes University(EBRU) were used. The outcome from the laboratory studies showed that carbon partitioning within isolated strains could be altered from carbohydrate to lipid which is more energy-rich. Hence, exploring the biodiesel production option using HRAOP MaB-floc biomass, which had a lipid content ranging between 12.1 ± 0.64 % and 13.9 ± 0.5 %, would require a preconditioning step in the form of nitrogen starvation to enhance its lipid content. Overall, the outcome of outdoor monitoring studies on biomass biochemical composition indicated that HRAOPs operating under natural environmental conditions preferentially generated a biomass rich in carbohydrate. Therefore, anaerobic digestion may be a more viable option for HRAOP MaB-floc biomass because of the high carbohydrate levels ranging between 24.9 ± 0.6 % and 25.6 ± 1.3 % of the dry MaB-floc biomass weight. Despite the low biomass C/N ratio (7.1 to 7.8), the MaB-floc biomass can be anaerobically co-digested with a higher C/N ratio (24) substrate such as in-pond digester sludge, to improve methane yields calculated to be between 0.31 m3 CH4/ kg MaB-floc biomass and 0.33 m3 CH4/ kg MaB-floc biomass. Anaerobic digestion of biomass also produces CO2 which can be recovered and added to HRAOPs to enhance MaB-floc biomass productivity while lowering greenhouse gas emissions from a wastewater treatment plant. The digestate from the anaerobic process, which is rich in nitrogen and phosphorus can be used as a biofertiliser. Thus, a potential MaB-floc biomass biorefinery consisting of biogas and bio-fertiliser pathways can be established using IAPS treating sewage as the platform technology. IAPS is a system designed to operate in a way that is passive and without substantial environmental impact but technological innovations and a reduction in the size of the system are required to make the technology more acceptable.
Keywords: Biomass energy; Waste products as fuel; Algal biofuels; Sewage -- Purification -- Nutrient removal